Adaptive Thermogenesis Driving Catch-Up Fat Is Associated With Increased Muscle Type 3 and Decreased Hepatic Type 1 Iodothyronine Deiodinase Activities: A Functional and Proteomic Study - Di Munno, Celia; Busiello, Rosa Anna; Calonne, Julie; Salzano, Anna Maria; Miles-Chan, Jennifer; Scaloni, Andrea; Ceccarelli, Michele; de Lange, Pieter; Lombardi, Assunta; Senese, Rosalba; Cioffi, Federica; Visser, Theo J.; et al. (Frontiers in Endocrinology, 2021)
Refeeding after caloric restriction induces weight regain and a disproportionate recovering of fat mass rather than lean mass (catch-up fat) that, in humans, associates with higher risks to develop chronic dysmetabolism. Studies in a well-established rat model of semistarvation-refeeding have reported that catch-up fat associates with hyperinsulinemia, glucose redistribution from skeletal muscle to white adipose tissue and suppressed adaptive thermogenesis sustaining a high efficiency for fat deposition. The skeletal muscle of catch-up fat animals exhibits reduced insulin-stimulated glucose utilization, mitochondrial dysfunction, delayed in vivo contraction-relaxation kinetics, increased proportion of slow fibers and altered local thyroid hormone metabolism, with suggestions of a role for iodothyronine deiodinases. To obtain novel insights into the skeletal muscle response during catch-up fat in this rat model, the functional proteomes of tibialis anterior and soleus muscles, harvested after 2 weeks of caloric restriction and 1 week of refeeding, were studied. Furthermore, to assess the implication of thyroid hormone metabolism in catch-up fat, circulatory thyroid hormones as well as liver type 1 (D1) and liver and skeletal muscle type 3 (D3) iodothyronine deiodinase activities were evaluated. The proteomic profiling of both skeletal muscles indicates catch-up fat-induced alterations, reflecting metabolic and contractile adjustments in soleus muscle and changes in glucose utilization and oxidative stress in tibialis anterior muscle. In response to caloric restriction, D3 activity increased in both liver and skeletal muscle, and persisted only in skeletal muscle upon refeeding. In parallel, liver D1 activity decreased during caloric restriction, and persisted during catch-up fat at a time-point when circulating levels of T4, T3 and rT3 were all restored to those of controls. Thus, during catch-up fat, a local hypothyroidism may occur in liver and skeletal muscle despite systemic euthyroidism. The resulting reduced tissue thyroid hormone bioavailability, likely D1- and D3-dependent in liver and skeletal muscle, respectively, may be part of the adaptive thermogenesis sustaining catch-up fat. These results open new perspectives in understanding the metabolic processes associated with the high efficiency of body fat recovery after caloric restriction, revealing new implications for iodothyronine deiodinases as putative biological brakes contributing in suppressed thermogenesis driving catch-up fat during weight regain.